Anaerobic digestion of biowastes in India: Opportunities, challenges and research needs. (15th April 2019) - Breitenmoser, Lena; Gross, Thomas; Huesch, Ragini; Rau, Julius; Dhar, Hiya; Kumar, Sunil; Hugi, Christoph; Wintgens, Thomas
Abstract: The quest for improved living conditions in rapidly growing Indian communities puts pressure on natural resources and produces emissions which harm the environment, society and the economy. Current municipal solid waste (MSW) practices are an important example, as most waste remains untreated and is often deposited on unsafe dumpsites or burned on open fires. Anaerobic digestion (AD) is an option to treat the large biodegradable fraction ('biowaste'). In rural parts of India, the technology to supply energy from biogas has been promoted for 30 years. Biowaste treatment in urban MSW management and organic fertilizer ('digestate') production for agriculture via AD have more recently gained attention but with limited success so far. Recent environmental policies in waste, energy, agricultural and other sectors have, however, set important cornerstones for a broader diffusion in the coming years. On the basis of peer-reviewed literature and governmental reports, we identify barriers and enabling factors along the AD chain (biowaste to technology to product utilization), and analyse relevant boundary conditions for the new multi-sector policies. We show that AD implementation has repeatedly failed due to unrealistic assumptions on biowaste quantity and quality, underestimation of the complex biowaste supply chain, unsuitable AD designs and overestimation of economic returns from biogas and digestate. Local knowledge and capacities for planning and process control are lacking in many places and resources required for operation and maintenance in the long run have often been ignored. We found that the multi-facetted value propositions of AD - including biowaste treatment, energy and fertilizer products - have only been partially tapped due to the exclusive focus on biogas. The new sector policies provide important enabling factors for change. Decentralized AD plants operating on a few tons biowaste per day from reliable and manageable sources (e.g. fruit and vegetable markets) could be a more promising step forward than large-scale investments which rely on large biowaste volumes from various sources. The parallel development of biowaste management, planning tools for municipalities, standardized digestate monitoring protocols and studies on simple, low-cost optimization measures for methane recovery from a wide range of biowastes and innovative high-solid AD digester designs will be prerequisites for the long-term future of AD projects. Highlights: Analysis of opportunities and challenges of anaerobic digestion (AD) plants in India. Review of India's renewable energy and biowaste management policies and programs. Review of biochemical methane potential studies from Indian biowaste. Identification of research needs alongside the AD value chains in India.